2019
DOI: 10.1136/bcr-2019-232944
|View full text |Cite
|
Sign up to set email alerts
|

Piperacillin–tazobactam induced bicytopenia in low cumulative treatment doses

Abstract: We present the case of infected wet gangrene of right foot in the setting of poorly controlled type 2 diabetes in a 71-year-old woman. This patient presented with improved infection condition after intravenous piperacillin–tazobactam (PTZ) 2.25 gm every 6 hours treatment and below knee amputation surgery on day 3. However, neutropenia and thrombocytopenia developed on day 13. We consulted a haematologist and performed a series of examinations. However, no significant findings were noted thereafter. PTZ was sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…1,3 Piperacillin, a member of the ureidopenicillin subclass, has been implicated in β-lactam-induced neutropenia more often than any other agent, with 246 cases. 2,3,5,29,31,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] Cases involving piperacillin or piperacillin-tazobactam were included in this count. Notably, a systematic review of piperacillin or piperacillin-tazobactam-induced neutropenia identified 183 cases using the Food and Drug Administration Adverse Event Reporting System.…”
Section: Incidence and Characteristicsmentioning
confidence: 99%
“…1,3 Piperacillin, a member of the ureidopenicillin subclass, has been implicated in β-lactam-induced neutropenia more often than any other agent, with 246 cases. 2,3,5,29,31,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] Cases involving piperacillin or piperacillin-tazobactam were included in this count. Notably, a systematic review of piperacillin or piperacillin-tazobactam-induced neutropenia identified 183 cases using the Food and Drug Administration Adverse Event Reporting System.…”
Section: Incidence and Characteristicsmentioning
confidence: 99%
“…3 Two of the prior studies reported bicytopenia with neutropenia and thrombocytopenia. 1,4 The other study reported a fall in only one cell line. All the patients reported a successful recovery in cell lines on the discontinuation of the medication.…”
mentioning
confidence: 96%
“…Ihtisham Qayum, MBBS 1 Awais Naeem, MBBS 1 Uzma Ikhtiar Khan, MBBS 1 Sohail Anwar, MBBS 1 Hafez M. Abdullah, MD 2 1 Internal Medicine Khyber Teaching Hospital Peshawar, Pakistan 2 Internal Medicine University of South Dakota Sanford School of Medicine Sioux Falls, SD…”
mentioning
confidence: 99%
See 2 more Smart Citations